Can there be a social contract with business? - Hodapp, Paul F. (Journal of business ethics, 1990)
Professor Donaldson in his book Corporations and Morality has attempted to use a social contract theory to develop moral principles for regulating corporate conduct. I argue in this paper that his attempt fails in large measure because what he refers to as a social contract theory is, in fact, a weak functionalist theory which provides no independent basis for evaluating business corporations. I further argue that given the nature of a morality based on contract and the nature of the modern corporation, it is highly unlikely that any plausible contract theory of business ethics can be developed.